Bilateral submandibular duct relocation for chronic sialorrhea: a 15 years of experience in children with a neurological disorder - Turki Imen Mehri (EDP Sciences, 2023)
Background: Chronic sialorrhea is a troublesome condition for children with neurological disorders that affect swallowing. Various surgical procedures for reflecting drooling cases are helpful. Some of them could be followed by complications or lead to over-dryness of the mouth. This article aims to highlight the safety and effectiveness of bilateral submandibular duct relocation (BSDR) on fifteen years of experience. Material and methods: A retrospective chart review identified 25 patients with chronic sialorrhea who underwent BSDR. Clinical and demographic data were reviewed. Surgical outcomes were assessed with both Wilkie and Brody's criteria and the Teacher drooling (TDS) scale. Results: The mean age of children was 11.7 years. They had neurological disorders and dribbled saliva with an average of 4.28 according to the TDS which falls to an average of 1.12 after surgery. By referring to Wilkie and Brody's criteria, 88% of the results have been labelled as excellent and good for the others. Conclusion: Our 15 years of experience in managing neurologically impaired children with profuse drooling illuminates and supports our trend for BSDR without sublingual gland excision. This surgical procedure is safe, and effective against drooling, protects oral health, and provides a high rate of success.